Hubungan Minat dengan Kunjungan Pemeriksaan IVA Test Pada Wanita Usia Subur di Wilayah Kerja UPTD Puskesmas Astanaanyar Kota Bandung - Novitasari, Dhini Wahyuni; Perania, Yanita (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Cervical cancer in second place with 36,633 cases or 9,2% of total cancer cases in Indonesia (WHO, 2022). The incidence of cervical cancer is most often found at the age of 45-54 years (42,40%). Coverage of cervical cancer screening using the IVA test in Indonesia is still very low at around 5%. The low number of early detection visits for cervical cancer is influenced by several factors, namely poverty, lavk of self-awareness, public knowledge and understanding regarding the dangers of cervical cancer, availability of information sources, support from health workers and family support. To determine interest in visiting IVA examinations for women of childbearing age in the UPTD working area of the Astanaanyar Health Center, Bandung City in 2023. This type of research in analytical qualitative research with a cross-sectional approach. The sample in this study was all women of childbearing age aged 30-50 years who were in the UPTD work area of the Astanaanyar Health Center In August 2023, totalling 94 people. The instrument is an interview sheet. Univariate and bivariate analysis with chi square test. It is known that almost all respondents did not make an IVA examination visit (80,9%) and most respondents were not interested in an IVA examination (59.6%) There is a relationship between interest and IVA examination visits  Keywords: Interest, IVA examinations, WUS  ABSTRAK Kanker serviks menempati urutan kedua terbanyak dengan jumlah 36.633 kasus atau 9,2% dari total kasus kanker di Indonesia (WHO,2022). Kejadian kanker serviks paling sering ditemukan yaitu pada usia 45-54 tahun (42,40%). Cakupan skrining kanker serviks menggunakan IVA test di Indonesia masih sangat rendah sekitar 5 %. Rendahnya kunjungan deteksi dini kanker serviks dipengaruhi oleh beberapa faktor yaitu kemiskinan, kurangnya kesadaran diri, pengetahuan dan pemahaman masyarakat mengenai bahaya kanker leher rahim, ketersediaan sumber informasi, dukungan tenaga kesehatan dan dukungan keluarga. Untuk mengetahui minat dengan kunjungan pemeriksaan IVA pada Wanita Usia Subur di Wilayah Kerja UPTD Puskesmas Astanaanyar Kota Bandung Tahun 2023. Jenis penelitian ini adalah penelitian kualitatif analitik dengan pendekatan crosssectional. Sempel dalam penelitian ini adalah semua wanita usia subur usia 30-50 tahun yang berada di wilayah kerja UPTD Puskesmas Astanaanyar pada bulan Agustus 2023 sebanyak 94 orang. Instrumen berupa lembar wawancara. Analisis univariat dan bivariat dengan uji chi square. Diketahui Hampir seluruh responden tidak melakukan kunjungan pemeriksaan IVA (80,9%) dan sebagian besar responden tidak minat terhadap pemeriksaan IVA (59,6%). Terdapat hubungan antara minat dengan kunjungan pemeriksaan IVA Kata Kunci: Minat, Pemeriksaan IVA, WUS